Effect of Early Initiation of Breastfeeding on Physiological Neonatal Jaundice in Infants Less than 14 Days of Age - Wahyu Utami Ekasari; Dhiyan Nany Wigati; Dewi Sapta Wati (Jurnal Profesi Bidan Indonesia, 2022)
Background: The infant mortality rate (AKB) is still high. Based on data from the Indonesian Ministry of Health in 2021 neonatal deaths were caused by low birth weight conditions (BBLR) of 35.2%, asphyxia (27.4%), infections (3.4%), congenital abnormalities (11.4), tetanus neonatorum (0.3%), and other causes (22.5%). Early breastfeeding is one of the efforts to reduce the risk of physiological jaundice, where the Initiation of Early Breastfeeding (IMD) is a baby starting to breastfeed on their own immediately after birth. Purpose: Analysis the Early Initiation of Breastfeeding Physiology Neonatal Jaundice in Infants less than 14 days of age.Methods: Analytical survey with cross sectional approach The number of samples in this study was 34 respondents. The data analysis used in the study is a simple linear regression. Results: From the results of the study in 34 respondents obtained results there is an influence between IMD on physiological neonatorum jaundice shown from the result p = 0.003 with a value of R square 0.241 means the influence of IMD on physiological neonatal jaundice of 24.1%. Conclusion: From the results of research in 34 respondents obtained results there is an influence between IMD on the jaundice of physiological neonatal